Profesionalisme Praktisi Baitul Mal Wa Tamwil di Kota Yogyakarta dan Kabupaten Sleman - Amir Mu'allim; M.Zainal Abidin (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2005)
This paper is the resume of a research which aimed to know the professionalism of BMT people in Yogyakarta city and Sleman regency. The type of the research is the qualitative which collected the data with questioner, depth interview and library research. As the qualitative research, the analysis data acted simultaneous with collecting the data, interpretation, and writing the research result. As the results that the interpretation of professionalism by many BMT people tends practically. The professionalism explained in the context of service quality given by BMT to its customers. Mean, the biggest professionalism measure is in service quality.